Imprisonment following discharge from mental health units: A developing trend in New Zealand - Skipworth, Jeremy; Garrett, Nick; Pillai, Krishna; Tapsell, Rees; McKenna, Brian (Frontiers in Psychiatry, 2023)
Introduction Contemporary models of care for people with mental disorders continue to shift to community-based care, requiring fewer inpatient mental health beds, shorter inpatient lengths of stay, and less use of coercion. It has been suggested that some mentally unwell people, whose behavior can no longer be safely contained in overstretched mental health units where seclusion and restraint are discouraged, are now left to the criminal justice system to manage. It is unclear whether the risk of imprisonment following discharge from a mental health unit has increased over recent years. Methods A quantitative, retrospective cohort study design was used to investigate any association between an acute inpatient mental health service admission in Aotearoa (New Zealand), and referral to a prison mental health team within 28 days of hospital discharge, from 2012 to 2020. Data were extracted from the national mental health dataset managed by the Ministry of Health. Results Risk of imprisonment within 28 days of inpatient discharge increased over the study period. People experiencing this outcome were more likely to be younger, male, of Mâori or Pacific ethnicity, presenting with substance use and psychotic disorders who were aggressive or overactive, and were subject to coercive interventions such as seclusion and compulsory treatment during their admission. Discussion We concluded that contemporary models of less coercive predominantly community based mental health care may be increasingly reliant on the criminal justice system to manage aggressive and violent behavior driven by mental illness. It is argued from a human rights perspective that mental health inpatient units should retain the capacity to safely manage this type of clinical presentation.